2020
DOI: 10.1111/ppe.12725
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with non‐nutritive sucking habits at 2 years of age among very preterm children: EPIPAGE‐2 cohort study

Abstract: Background The association between prolonged non‐nutritive sucking habits (NNSHs, ie, sucking pacifiers or fingers) and maxillofacial growth anomalies in the general population has been widely described. Because maturation of sucking abilities is not fully achieved in very preterm infants (<32 weeks’ gestation), neonatal services worldwide rely on the use of pacifiers to promote the development of adequate sucking reflexes, possibly prolonging NNSHs during infancy. Objective We aimed to describe the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Pacifier sucking is common and even recommended in infants born very preterm during neonatal hospitalization to support maturation of oro-facial motor function and to minimize pain (18)(19)(20). The frequency of NNSHs during infancy seems higher in infants born preterm than those born full-term (21).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Pacifier sucking is common and even recommended in infants born very preterm during neonatal hospitalization to support maturation of oro-facial motor function and to minimize pain (18)(19)(20). The frequency of NNSHs during infancy seems higher in infants born preterm than those born full-term (21).…”
Section: Introductionmentioning
confidence: 84%
“…Breastfeeding was associated with less NNSHs in children born very preterm (21). The recent studies of preterm children and the general population in Brazil concluded shorter duration of breastfeeding associated with increased risk of malocclusions (including posterior crossbite) at the age of 5 (25,49).…”
Section: Neonatal Factors and Maxillofacial Growth Anomaliesmentioning
confidence: 93%
See 1 more Smart Citation